L’influence Des Pratiques Marketing Des Laboratoires Pharmaceutiques Sur L’éthique De La Fonction Médicale Au Maroc - Eddine, Mohammed Saad; Ammi, Anouar (European Scientific Journal, ESJ, 2018)
In Morocco and unlike the first world countries, and with the absence of the ethical code of medical promotion, a lot of pharmaceutical companies use the gifts policy in order to influence the doctors prescribing to the patients. Concerning the Moroccan pharmaceutical industry, a study made by the competition council in 2011 showed that the existence of dubious practices that goes against the patient’s interest. These practices are often materialized by public relations actions between the stakeholders operating in the medical field in the doctor’s favor, especially the aspects of the heavy and expensive pathologies. While medicine is usually governed by some very strict rules of ethnics and morals, this article aims to analyze the nature of the links that governs the relationship between the pharmaceutical laboratories and the doctors of different specialties; different scales and different areas in Morocco. The article will present a set of elements that demonstrate on the basis of the sample studied that the relationship between the various stakeholders operating in the medical sector is still not healthy, and that it is strongly impacted by material interests. to the detriment of patients, hence the need to involve professional and state actors for the implementation of a strict ethical code.